2010
DOI: 10.1590/s0034-737x2010000500009
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade de acaricidas utilizados em cafeeiro para larvas de crisopídeos

Abstract: Seletividade de acaricidas utilizados em cafeeiro para larvas de crisopídeos Rev. Ceres, Viçosa, v. 57, n.5, p. 621-628, set/out, 2010 RESUMO ABSTRACTS Selectivity of acaricides used in coffee crops to green lacewingGreen lacewings are commonly found in coffee agroecosystems feeding on several pests of economic importance. The objective of this study was to evaluate the selectivity of acaricides used in coffee crop to Chrysoperla externa (Hagen, 1861). The treatments consisted of control (water), spirodiclofen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Most of the studies available in the literature on the selectivity of insecticides to the natural enemies of the coffee tree, approach the selectivity in favor of predators, such as the predatory wasps of leaf miner (GUSMÃO et al, 2000;FRAGOSO et al, 2001), chrysopides (VILELA et al, 2010) and lady bug (ROCHA et al, 2010;. In other cultures, studies have shown that cartap may reduce parasitism (PASINI et al, 2017) and affect the sex ratio (CARVALHO et al, 2003) of Trichogramma pretiosum Riley in tomato.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies available in the literature on the selectivity of insecticides to the natural enemies of the coffee tree, approach the selectivity in favor of predators, such as the predatory wasps of leaf miner (GUSMÃO et al, 2000;FRAGOSO et al, 2001), chrysopides (VILELA et al, 2010) and lady bug (ROCHA et al, 2010;. In other cultures, studies have shown that cartap may reduce parasitism (PASINI et al, 2017) and affect the sex ratio (CARVALHO et al, 2003) of Trichogramma pretiosum Riley in tomato.…”
Section: Resultsmentioning
confidence: 99%
“…Integrated pest management has one of its basic components in the selectivity of insecticides, allowing the preservation of natural enemies. Studies on the selectivity of phytosanitary products recorded for coffee cultivation have been specifically developed in favor of predators (ROCHA et al, 2010;VILELA et al, 2010;CASTILHOS et al, 2017), and there is a lack of information about the effects on parasitoids.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, few studies have been addressed that all developmental stages (eggs, larva, pupa, and adult) of green lacewing are susceptible to insecticides, the exposure may lead to lethal and sub-lethal effects [7,12]. Most of the studies highlighted lethal and sub-lethal effects of selective insecticides on larvae and adult lacewing [13][14][15], and some have focused on eggs and pupae that can be considered more tolerant to insecticides [6,16,17].…”
Section: Introductionmentioning
confidence: 99%